Cytostatic and immunomobilizing activities of polymer-bound drugs: experimental and first clinical data - Ríhová, Blanka; Strohalm, Jirí; Prausová, Jana; Kubácková, Katerina; Jelínková, Markéta; Rozprimová, Lad'ka; Sírová, Milada; Plocová, Dana; Etrych, Tomás; Subr, Vladimír; Mrkvan, Tomás; Kovár, Marek; et al. (Journal of controlled release, 2003)
An N-(2-hydroxypropyl)methacrylamide (HPMA) copolymer carrier containing doxorubicin and human immunoglobulin as an actively/passively targeting moiety was used in four patients with generalized breast cancer resistant to standard cytotoxic chemotherapy. The dose and time schedule were deduced from a Phase I clinical trial in which doxorubicin bound to HPMA copolymer carrier (PK1) was tested. It was confirmed that the Dox-HPMA-HuIg conjugate is stable and doxorubicin remains in the peripheral blood with a small amount also in the urine, mostly in its polymer-bound form. More than 116 biochemical, immunological and hematological parameters were determined for blood samples taken from patients 24 h, 48 h, 72 h and 1 to 11 weeks after treatment. Depending on the patient, some parameters decreased permanently or temporarily to the normal level (CRP, C3, CA 72-4, beta(2)-microglobulin, ferritin, CEA, CA 125, CD4, CD8, CE19, CD16(+)56(+), leu, ery) and some moved markedly towards physiological values (AST, ALT, ALP, GMT, CA 15-3, NSE, AFP). While the number of peripheral blood reticulocytes was significantly decreased after treatment with the classical free drug, their number was not affected or was even elevated after treatment with Dox-HPMA-HuIg. Increased absolute numbers of CD16(+)56(+) and CD4(+) cells in the peripheral blood and activation of NK and LAK cells in all patients support data obtained in experimental animals, pointing to a dual, i.e. cytostatic and immunomobilizing character of Dox-HPMA conjugates containing a targeting immunoglobulin moiety.
Keywords: doxorubicin; pomocné látky; Immunoglobulin G; monoklonální protilátky; protinádorové látky; protinádorová antibiotika; Liver Function Tests; jaterní testy; Adult; Excipients; imunoglobulin G; dospělí; nádory prsu; methakryláty; krevní obraz; buňky K aktivované lymfokiny; Thymidine; imunoglobuliny; ELISA; mastektomie; Polymers; Killer Cells, Lymphokine-Activated; Blood Cell Count; Enzyme-Linked Immunosorbent Assay; Animals; lidé; ženské pohlaví; polymery; Breast Neoplasms; Humans; zvířata; buňky NK; Antibiotics, Antineoplastic; nádorové buňky kultivované; myši; thymidin; Tumor Cells, Cultured; Antibodies, Monoclonal; Mastectomy; Mice; Female; Immunoglobulins; Killer Cells, Natural; Methacrylates; lidé středního věku; Doxorubicin; Antineoplastic Agents; Middle Aged